Soil Fertility and Biodiversity of Arbuscular Mycorrhizal Fungi Associated with Cashew’s (Anacardium occidentale L.) Cultivars Characteristics in Benin (West Africa) - BALOGOUN, IBOURAIMAN; SAIDOU, ALIOU; KINDOHOUNDE, NARCISSE; AHOTON, ESSÈHOU LÉONARD; AMADJI, LUCIEN GUILLAUME; AHOHUENDO, BONAVENTURE COHOVI; BABATOUNDE, SÉVÉRIN; CHOUGOUROU, CHÈPO DANIEL; BABA-MOUSSA, LAMINE SAÏD; AHANCHEDE, ADAM (My University, 2015)
The present study aims to assess the biodiversity of arbuscular mycorrhizal fungi (AMF) associated with cashew (Anacardium occidentale L.) cultivars characteristics in Benin (West Africa). 108 soil samples were collected at 0-20, 20-40 and 40-60 cm depth under cashew trees at Glazoué in the centre Benin. Cashew’s cultivars characteristics regarding nut and apple size, apple colors and classes of Diameter at Breast Height (DBH) were the treatments. Soil chemical properties, AMF spores’ density and the diversity of AMF in the soil were assessed. Plantation of cashew improved the stock of soil organic carbon (11.24±0.63 and 10.93±0.71 g/kg for 0-20 cm soil depth respectively for cultivars producing big nuts and big apples and cultivars producing small nuts and small apples) and total nitrogen content (1.29±0.11 and 1.21±0.12 g/kg for 0-20 cm soil depth respectively for cultivars producing big nuts and big apples and cultivars producing small nuts and small apples) but it depletes available phosphorus (36.86±6.53 and 41.42±9.22 mg/kg for 0-20 cm soil depth respectively for cultivars producing big nuts and big apples and cultivars producing small nuts and small apples) and exchangeable potassium (0.93±0.10 and 0.79±0.04 cmol/kg for 0-20 cm soil depth respectively for cultivars producing big nuts and big apples and cultivars producing small nuts and small apples). Seven species of AMF (Scutelospora gregarine, Acaulospora colossica, Acaulospora lacunosa, Enthrophospora infrequens, Glomus hoi, Glomus geosporum and Glomus sp.) were identified. They belong to three families and four genera. The species belonging to Glomeracea family were dominants (91.8%) against 5.5% and 2.7% respectively for the Gigasporaceae and Acaulosporaceae. In general, the average numbers of AMF spores were 5.63±0.26; 3.54±0.19 and 1.94±0.15 per gramme of dry soil respectively for 0-20, 20-40 and 40-60 cm depth. The community of AMF was fairly diversified in the soil under cashew’s trees. There was an equitable distribution of AMF genera associated with cashew’s cultivars characteristics tree.
Keywords: Cashew plantation; Shannon-Wiener diversity index; Pielou index; land-use system; tropical ferruginous soils.